Rancangan Kinerja Technical Staff Sebagai Productivity Improvement Pada Line Produksi Garmen Lingerie Dengan Metode Failure Mode And Effect Analysis (FMEA) - Urbaningtyas Ragadini (Jupiter: Publikasi Ilmu Keteknikan Industri, Teknik Elektro dan Informatika, 2024)
PT XXX is a garment company on an international scale. Technical staff plays an important role in maintaining operational performance, especially in facing challenges during rapid style changes and potential operational risks. This research aims to identify the causes of low productivity of technical staff performance, design improvement strategies with a focus on productivity improvement, and evaluate the effectiveness of the Failure Mode and Effect Analysis (FMEA) method in improving the technical performance of technical staff. The results of this research show that the FMEA method is effective in identifying potential failures, helps evaluate the level of risk by calculating the Risk Priority Number (RPN) value, and is a reliable tool for designing strategies to improve technical staff performance.